PHYTOCHEMICAL ANALYSIS AND EVALUATION OF IN VITRO IMMUNOMODULATORY ACTIVITY OF RHODODENDRON ARBOREUM LEAVES - Rawat, Pramod; Bachheti, Rakesh Kumar; Kumar, Navin; Rai, Nishant (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objectives: The objectives of this study are to analyze phytoconstituents in Rhododendron arboreum leaves (qualitatively and quantitatively) and to estimate the immunomodulatory effects of extracts using different in vitro methods for intracellular and phagocytic killing potency of neutrophils, which are subsequent, involved in the process of phagocytosis by neutrophils. Methods: R. arboreum leaves extracts were separately extracted in 100% methanol, 50% methanol, and aqueous by a hot percolation technique using Soxhlet apparatus and concentrated with a vacuum rotary evaporator apparatus. The percentage yield of the extracts wares calculated. The extract was used to analyze phytoconstituents qualitatively, and total phenolic and flavonoid content were estimated. In another study, already purified methanolic extract of R. arboreum leaves, namely cytoplasmic male sterility (CMS-3) (kaempferol), RAM fr2, and transcranial magnetic stimulation (TMS-10) (ursolic acid) was used to evaluate immunomodulatory activities by nitroblue tetrazolium test, phagocytosis of killed Candida albicans. Results: Phytochemical screening of the extracts showed the presence of major classes of phytochemicals, i.e., phytosterols, flavonoids, phenols, alkaloids, carbohydrate, glycoside, sterols and steroids, terpenoids, and tannin while saponin was absent in all extract. The percent yield of leaves extract was 12.97%. Total phenolic content (TPC) expressed as gallic acid equivalents (GAE) ranged 1327.5±0.009 (in 100% methanolic extract), 1309.5±0.011 (in 50% methanolic), and 1468.5±0.006 mg GAE g−1 dry weight (in aqueous extract). Total flavonoid content expressed as rutin equivalents (RE) ranged 219±0.025 (in 100% methanolic extract), 184±0.02 (in 50% methanolic), and 262±0.58 mg (in aqueous extract) mg RE g−1 dry weight. R. arboreum purified extract CMS-3 (kaempferol), RAM fr2, and TMS-10 (ursolic acid) stimulated the neutrophils to phagocytic activity to the extent of 67.67±2.08%, 40.3±1.5%, and 79.67±0.57%, respectively. The above-said extracts stimulated the phagocytosis of killed C. albicans. The mean particle numbers for CMS- 3, RAM fr2, and TMS-10 were found to be 6.7, 6.3, and 7, respectively, at concentration 1 mg/ml. Conclusion: The phytochemical screening of all the extracts showed the presence of various phytochemicals that are biologically important. The total phenolic and flavonoid content of the plant are comparable to other medicinal plants. Even though the enormous progress on the phytochemistry and pharmacology of R. arboreum have been made, there still require more conclusive studies on the safety, efficacy, and in vivo toxicity of extracts and pure compounds to gain a better understanding.